The Hypothetical Dialogue Style Of The Arabic Grammarian Al-Muradi/ سلوب الحوار الافتراضي عند النحوي العربي المرادي - Mohammad Shaker Mahmoud; Abdullah Hameed Addalimi (Ijaz Arabi Journal of Arabic Learning, 2026)
This study examines the hypothetical dialogue method employed by skilled grammarians, including al-Muradi in his book "Tawdih al-Maqasid wa al-Masalik" (Clarification of Objectives and Paths). This method, also known as "al-Fanqala," is derived from the expression "If it is said or you say...I say." Its purpose is to highlight grammatical, morphological, and other issues, presenting the content of the scholarly matter. Its aim is to familiarize readers with a hypothetical questioning approach that reinforces understanding and provides comprehensive answers. It also stimulates analytical thinking and the development of meaning among learners by presenting and discussing diverse issues. Sibawayh (d. 180 AH) was among the first to utilize this method. Therefore, it was essential to delve into al-Muradi's hypothetical dialogue, exploring its nature, details, and discussion of grammatical issues. He relied on Quranic verses, hadiths, metrical poetry, and Arabic proverbs to support his arguments. The research concludes with a summary of its findings.